Serum paraoxanase-1 activity in patients with acute otitis media - Abdullah Taskin (Journal of Clinical and Experimental Investigations, 2011)
Objectives: Paraoxonase is a high-density lipoprotein (HDL)-associated antioxidant enzyme. We aimed to compare the activity of serum paraoxanase-1 (PON 1) in healthy controls and patients with acute otitis media (AOM).Subjects and methods: We performed a prospective controlled trial in patients with AOM. A total of 60 subjects, 30 patients with AOM (17 male; age, 15 ± 9 years) and 30 age- and sex-matched controls (16 male; age, 16 ± 5 years) were enrolled in this study. PON 1 activity was measured using Mackness’ methods.Results: PON 1 activity was significantly lower in the AOM group compared to control group (155 ± 95 U/L vs. 210 ± 96 U/L, P=0.04).Conclusions: The present study demostrates that serum PON 1 activity is low in AOM, similar to other conditions with increased oxidative stress. We speculate that PON 1 enzyme is consumed at a greater rate during AOM in order to prevent increased oxidative damage. J Clin Exp Invest 2011; 2 (4): 412-415